Hubungan Tingkat Pengetahuan Kesehatan Reproduksi Remaja dengan Sikap Seksual Pranikah di SMK Taman Siswa Nanggulan Tahun 2017 - Handhika, Putri; Suherni, Suherni; Sumarah, Sumarah (Jurnal Kesehatan Ibu dan Anak, 2017)
The number of adolescents in Indonesia is estimated to have reached 62 million people. The current problem of reproductive health knowledge is so complex that it is demonstrated in the outcomes of the 2012 KRR SDKI that adolescent knowledge of reproductive health is inadequate, which can be seen by only 35.3% of female adolescents and 31.2% of boys aged 15- 19 years of knowing that women can get pregnant with one sexual intercourse. The purpose of this research is to know the correlation of knowledge of adolescent reproduction health with premarital sexual attitude at SMK Taman Siswa Nanggulan in 2017. This Research Method is Analytical Survey, research type using Observasional with cross sectional time approach, sampling using purposive sampling that is used subject in the case of 80 adolescents The number of samples was determined by using different proportional hypothesis test (Lemeshow 1997) The minimum sample found for this study was 72 respondents plus 10% to become 80 respondents. Data collection used questionnaires distributed to respondents, analyzed using univariate and bivariate analysis using chi-square analysis. The results of the study there is a significant relationship between knowledge of adolescent reproductive health with premarital sexual behavior, p-value 0.000. This research can be concluded that there is correlation of level of knowledge of reproductive health of adolescent significant with premarital sexual attitude.